2019
DOI: 10.1111/poms.13082
|View full text |Cite
|
Sign up to set email alerts
|

On the Competition between Two Modes of Product Recovery: Remanufacturing and Refurbishing

Abstract: The markets for recovered products in China typically consist of both remanufactured and refurbished products. The government requires that the remanufactured product match the quality level of the new product, while no such requirements exist for the refurbished product. Furthermore, remanufacturing is a relatively new phenomenon in China, whereas the refurbishing industry is old, widespread, and largely unregulated. Compared to the new product, the two types of recovered products enjoy a cost advantage, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 17 publications
0
57
0
Order By: Relevance
“…Remanufacturing is recognized as the most effective product recovery option and studied by many scholars. Some scholars focus on introducing remanufacturing market [23], optimizing remanufacturing cost [7], the consumer's perceived value of the remanufactured product [24], the production and pricing of the remanufactured product [25,26], and economic profit [27][28][29]. Wang et al [3] found that the manufacturer disposes the used products by recycling, remanufacturing, and innocent treatment and determines the optimal portfolio of product recovery options and environmental impacts of different portfolios.…”
Section: Operation Management Of the Epr Systemmentioning
confidence: 99%
“…Remanufacturing is recognized as the most effective product recovery option and studied by many scholars. Some scholars focus on introducing remanufacturing market [23], optimizing remanufacturing cost [7], the consumer's perceived value of the remanufactured product [24], the production and pricing of the remanufactured product [25,26], and economic profit [27][28][29]. Wang et al [3] found that the manufacturer disposes the used products by recycling, remanufacturing, and innocent treatment and determines the optimal portfolio of product recovery options and environmental impacts of different portfolios.…”
Section: Operation Management Of the Epr Systemmentioning
confidence: 99%
“…e market size is normalized to 1. Consumers typically value the remanufactured product less than the new product [6,[28][29][30]. us, we assume that if a consumer is willing to pay θ for a new product, then his WTP for a remanufactured product is δθ, where δ(0 < δ < 1) is a discount factor for the remanufactured product.…”
Section: Consumersmentioning
confidence: 99%
“…It can be seen that the existing studies at home and abroad are based on the assumption that remanufacturing is the only recycled product in the market, ignoring the fact that there may be low-quality recycled products in the actual market. In order to better analyze the development dilemma and complex market environment faced by Chinese remanufacturing enterprises, our research team studied the market competition of remanufacturing, renovation, and new products ( Chen and Chen, 2019 ) with a theoretical modeling method on the one hand, and analyzed Chinese consumers’ remanufacturing purchasing behavior and decision-making process with an empirical method on the other hand ( Chen et al, 2019 ). This paper introduces the purchase experiment in our empirical study, examines the process of consumers’ purchase of different products, and studies the influence of refurbished products on the purchase choice of remanufactured products and the influencing factors of consumers’ WTP for remanufactured products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the definition of product recycling by Thierry et al (1995) , Ortegon et al (2014) , the product recycling method can be divided into five categories: repair, refurbishing, remanufacturing, cannibalization, and recycling ( Figure 1 ) according to the disassembly degree of the product in the process. Among them, the purpose of refurbishment is to recycle the used products and to continue to put them into the market after reaching a certain quality standard, which is lower than the quality standard of the new product; the purpose of remanufacturing is to make the second-hand products meet the same quality standards of the new products before putting them into the market ( Chen and Chen, 2019 ).…”
Section: Introductionmentioning
confidence: 99%